C4d immunohistochemical stain of formalin‐fixed paraffin‐embedded tissue as a sensitive method in the diagnosis of bullous pemphigoid. (24th May 2019) - Kamyab, Kambiz; Abdolreza, Mona; Ghanadan, Alireza; Mortazavi, Hossein; Nikoo, Azita; Motavalli, Farhad; Nasimi, Maryam
Abstract: Background: Bullous pemphigoid (BP) is the most common type of subepidermal bullous disease. Direct immunofluorescence (DIF) is the gold standard for diagnosis, but it requires a fresh tissue specimen. This study was conducted to evaluate the accuracy of using immunohistochemical (IHC) analysis for the detection of C4d in paraffin‐embedded tissue of BP cases. Methods: A retrospective study was performed on 30 BP cases (confirmed by Hematoxylin and eosin [H&E] and DIF) and 30 controls. IHC studies were performed on formalin‐fixed paraffin‐embedded (FFPE) tissues. Results: Of 30 BP patients (11 male and 19 female), 27 (90%) were C4d positive and three patients (10%) were C4d negative. The C4d deposits were seen as linear brown stain along the dermoepidermal junction (18 cases), around basal keratinocytes (eight cases), or Civatte‐like (three cases). Two cases revealed more than one pattern in IHC staining. Of 30 control specimens, 26 (86%) cases were C4d negative and four (13.4%) were positive for granular deposits of C4d which were diagnosed as dermatitis herpetiformis. Conclusion: C4d IHC study is a valuable diagnostic tool with sensitivity of 90% and specificity of 86.7%, and is especially useful in cases in which frozen specimens are not available or FFPE specimens are the only available material for analysis.